2016
DOI: 10.5114/wiitm.2016.64640
|View full text |Cite
|
Sign up to set email alerts
|

Post-laparoscopy predictive factors of achieving pregnancy in patients treated for infertility.

Abstract: IntroductionLaparoscopy is a long-established diagnostic and therapeutic method for treating women suffering from infertility. The application of this method of treatment can help achieve pregnancy only if there is correct classification of patients and evaluation of their partner’s reproductive capacity. The main predictors of achieving pregnancy in a couple treated for infertility are the woman’s age, her ovarian reserve, tubal patency, the presence of endometriosis and quality of sperm parameters.AimTo eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A total of 17 studies were therefore included at final analysis, for a total of 968 patients with endometrioma and 1874 patients in the control group (Table 1) (18, 19, 26, 28, 41-53). Twelve studies were prospective studies (18, 19, 28, 42-47, 49, 51, 53) and five were retrospective studies (26,41,48,50,52). Six studies included in the control group only patients with non-endometriosis benign ovarian cysts (19,42,46,(49)(50)(51).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 studies were therefore included at final analysis, for a total of 968 patients with endometrioma and 1874 patients in the control group (Table 1) (18, 19, 26, 28, 41-53). Twelve studies were prospective studies (18, 19, 28, 42-47, 49, 51, 53) and five were retrospective studies (26,41,48,50,52). Six studies included in the control group only patients with non-endometriosis benign ovarian cysts (19,42,46,(49)(50)(51).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of AMH in human reproduction is confirmed by research of Hussain et al, Lehmann et al, Reichmanm et al, and Wdowiak et al, which indicate that the chance for achieving pregnancy grows together with an increase in the level of AMH in the case of treatment by the in vitro fertilization method. The abovementioned studies did not unequivocally show whether FSH or AMH has a greater predictive value in achieving pregnancy [ 10 , 27 , 28 , 29 ]. In this study, women with very high AMH (polycystic ovarian syndrome) and those with lowered levels of this hormone (premature menopause) were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of estradiol is conditioned by an adequate ovarian reserve, which is assessed by means of AMH, FSH, and LH. Many scientific reports have analyzed ovarian reserve in the context of achieving pregnancy during infertility treatment [ 9 , 10 ]. Interactions between E2 and P are dependent on the ovarian reserve, and that, as well as a premature rise of progesterone during ovulation, can affect conception [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…During a study by Wdowiak, A. et al, based on a logistic regression analysis, it was found that together with an increase in such variables as semen density, percentage of morphologically normal spermatozoa, and progressive motility in ejaculate, and the anti-mullerian hormone (AMH) level in female partners, the chance for achieving pregnancy increased, and these relationships were statistically significant. Regarding the case of a partner’s age, viability, mixed antiglobulin reaction (MAR) test for immunoglobulin (Ig)A and IgG, no relationship was observed with achieving pregnancy [ 41 ]. Summing up, considering the classic assessment of semen parameters, it cannot be unequivocally determined as to what extent a decrease in semen parameters would affect the reproductive ability of males with inflammatory bowel diseases.…”
Section: Discussionmentioning
confidence: 99%